لمحات عن دراسة ألا الاستفتاحية في سورة هود وإلا الاستثنائية في سورة البقرة - Mulyani Maiza; Hanomi Hanomi; Yufni Faisol (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2025)
Abstract God has revealed the Qur'an in a clear Arabic tongue, and its language is classical Arabic. The Arabic language became the most important thing to understand the intention of the Qur'an. In this research discusses the word